Online Learning and Open Education: Transforming Beyond Digitalization - Afifi, Abdullah A; Arifin, Nor Anisa; Eliza, Mona; Azami, Evan; Salm, Gustian (IDRIS Darulfunun Institute, 2024)
The global shift toward digital transformation has significantly accelerated the adoption of online learning and open education models. However, in an increasingly complex and fast-changing world (VUCA), digitalization alone is no longer sufficient as an objective. This article aims to explore how online learning and open education can evolve beyond digitalization by aligning with broader global challenges, trends, and emerging societal needs. Using a conceptual and literature-based approach, the paper examines how open education contributes to contemporary issues such as technological advancement, sustainability, regional development, inclusiveness, and public participation. In this context, open education is not merely defined by free access to digital platforms but rather as a paradigm shift toward collaboration, open knowledge, and democratized learning. Education is increasingly understood as a participatory and sustainable ecosystem, rather than a one-directional process. This study emphasizes that building an inclusive, adaptive, and future-relevant education system requires the integration of policy innovation, technological advancement, and values of openness. The article provides practical policy insights, implications, and strategic recommendations for transitioning from simple digital educational access to a development and transformation strategy, particularly in developing countries where educational inequality and sustainability gaps remain key concerns.